Islet Encapsulation: New Developments for the Treatment of Type 1 Diabetes - Zhang, Qi; Gonelle-Gispert, Carmen; Li, Yanjiao; Geng, Zhen; Gerber-Lemaire, Sandrine; Wang, Yi; Buhler, Leo (Frontiers in Immunology, 2022)
Islet transplantation is a promising approach for the treatment of type 1 diabetes (T1D). Currently, clinical islet transplantation is limited by allo - and autoimmunity that may cause partial or complete loss of islet function within a short period of time, and long-term immunosuppression is required to prevent rejection. Encapsulation into semipermeable biomaterials provides a strategy that allows nutrients, oxygen and secreted hormones to diffuse through the membrane while blocking immune cells and the like out of the capsule, allowing long-term graft survival and avoiding long-term use of immunosuppression. In recent years, a variety of engineering strategies have been developed to improve the composition and properties of encapsulation materials and to explore the clinical practicality of islet cell transplantation from different sources. In particular, the encapsulation of porcine islet and the co-encapsulation of islet cells with other by-standing cells or active ingredients for promoting long-term functionality, attracted significant research efforts. Hydrogels have been widely used for cell encapsulation as well as other therapeutic applications including tissue engineering, cell carriers or drug delivery. Here, we review the current status of various hydrogel biomaterials, natural and synthetic, with particular focus on islet transplantation applications. Natural hydrophilic polymers include polysaccharides (starch, cellulose, alginic acid, hyaluronic acid, chitosan) and peptides (collagen, poly-L-lysine, poly-L-glutamic acid). Synthetic hydrophilic polymers include alcohol, acrylic acid and their derivatives [poly (acrylic acid), poly (methacrylic acid), poly(acrylamide)]. By understanding the advantages and disadvantages of materials from different sources and types, appropriate materials and encapsuling methods can be designed and selected as needed to improve the efficacy and duration of islet. Islet capsule transplantation is emerging as a promising future treatment for T1D.